2009
DOI: 10.1021/la8031122
|View full text |Cite
|
Sign up to set email alerts
|

XPS and SPR Analysis of Glycoarray Surface Density

Abstract: Despite the fact that the carbohydrate microarray has seen increasing use within the field of glycobiology, the surface chemistry of the glycoarray remains largely unexplored. Motivated by the need to develop surface analytical techniques to characterize carbohydrate-modified surfaces, we developed a quantitative X-ray Photoelectron Spectroscopy (XPS) and Surface Plasmon Resonance imaging (SPR imaging) method to study glycan biosensors. We performed a comparative analysis on the relative coverage of mixed self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 39 publications
5
88
0
Order By: Relevance
“…[3] However, several questions regarding the effects of different immobilization chemistries, glycan density and display, on protein binding remain unanswered. Surface chemistry has become increasingly important because several groups have shown that glycan display [4,5] and density [6] are involved in glycan-protein recognition events that can affect binding outcomes. In this report, we addressed the following questions: First, how important is the length of the spacer that separates the glycan from the imprinted surface?…”
mentioning
confidence: 99%
“…[3] However, several questions regarding the effects of different immobilization chemistries, glycan density and display, on protein binding remain unanswered. Surface chemistry has become increasingly important because several groups have shown that glycan display [4,5] and density [6] are involved in glycan-protein recognition events that can affect binding outcomes. In this report, we addressed the following questions: First, how important is the length of the spacer that separates the glycan from the imprinted surface?…”
mentioning
confidence: 99%
“…This phenomenon is probably related to the increase expected from multivalent binding. 21,18,57 On crystalline silicon, we demonstrate that the optimum conditions for multivalent interactions is a compromise between the surface concentration of glycan ligands in terms of density and spacing. 59 This effect gives rise to a maximum efficiency in the concentration range 3−9 × 10 13 cm −2 for bivalent interaction of mannose with Lens culinaris lectin.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…Recently, several microarray platforms with nonfluorescence detection techniques including mass spectrometry (MS) [25,39,78,79], surface plasmon resonance (SPR) [52,53,[80][81][82][83], scanning ellipsometry (imaging) [84], and resonant light scattering (RLS) of nanoparticle [85,86], have developed for glycomic analysis. For instance, Cheng and coworkers reported the fabrication of a carbohydrate microarray with surface plasmon resonance imaging (SPRi) detection system for studying interactions of carbohydrates with lectins (see Fig.…”
Section: Labeling and Detection Methodsmentioning
confidence: 99%